2011
DOI: 10.1016/j.semcdb.2011.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Mediator and human disease

Abstract: Since the identification of a metazoan counterpart to yeast Mediator nearly 15 years ago, a convergent body of biochemical and molecular genetic studies have confirmed their structural and functional relationship as an integrative hub through which regulatory information conveyed by signal activated transcription factors is transduced to RNA polymerase II. Nonetheless, metazoan Mediator complexes have been shaped during evolution by substantive diversification and expansion in both the number and sequence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
70
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 158 publications
(183 reference statements)
0
70
0
Order By: Relevance
“…In addition, how a single complex can be involved in ensuring tight transcriptional regulation of hundreds or thousands of genes through different specific interactions with TFs is largely unknown. The importance of the complex is highlighted by the fact that many Mediator subunits are involved in human diseases like neurodevelopmental pathologies or cancers (Kaufmann et al 2010;Hashimoto et al 2011;Spaeth et al 2011;Schiano et al 2014).…”
mentioning
confidence: 99%
“…In addition, how a single complex can be involved in ensuring tight transcriptional regulation of hundreds or thousands of genes through different specific interactions with TFs is largely unknown. The importance of the complex is highlighted by the fact that many Mediator subunits are involved in human diseases like neurodevelopmental pathologies or cancers (Kaufmann et al 2010;Hashimoto et al 2011;Spaeth et al 2011;Schiano et al 2014).…”
mentioning
confidence: 99%
“…In addition to ID, FG and Lujan syndromes share several overlapping clinical manifestations, including agenesis/dysgenesis of the corpus callosum, macrocephaly, hypotonia, craniofacial dysmorphisms, seizures, and behavioral disturbances (3,4). Although neither condition was originally considered in the differential diagnosis of the other, these two syndromes were recently found to be allelic, arising from different missense mutations in the Xq13 gene encoding MED12, a subunit of the RNA polymerase II transcriptional Mediator (3)(4)(5).…”
mentioning
confidence: 99%
“…Furthermore, MED12 has been implicated in vertebrate neural development, and genetic variation in MED12 is associated with neuoropsychiatric illness, including schizophrenia and psychoses, in humans (5,13). However, the underlying basis by which genetic disruption of MED12 elicits the broad spectrum of clinical phenotypes observed in FG and Lujan syndromes remains unknown.…”
mentioning
confidence: 99%
“…Activity of the Mediator complex is required to express RNA-polymerase II-transcribed genes in the presence of gene-specific activators by promoting preinitiation complex assembly. 2 As a result of the Med30 mutation, the authors observed a progressive decline in the transcription of genes specifically involved in oxidative phosphorylation and mitochondrial integrity. The transcriptional profile of the left ventricle of the 5 weeks old homozygous mutant mice displayed a considerable reduction in Ppargc1␣ and Esrra transcripts, which code for PGC1␣ (peroxisome proliferator-activated receptor-␥ coactivator-1␣) and ERR␣ (estrogen-related receptor-␣), respectively.…”
mentioning
confidence: 99%